2014
DOI: 10.4103/0970-0358.138961
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for blood volume estimation using trivalent chromium in rabbit models

Abstract: Background:Blood volume measurement though important in management of critically ill-patients is not routinely estimated in clinical practice owing to labour intensive, intricate and time consuming nature of existing methods.Aims:The aim was to compare blood volume estimations using trivalent chromium [51Cr(III)] and standard Evans blue dye (EBD) method in New Zealand white rabbit models and establish correction-factor (CF).Materials and Methods:Blood volume estimation in 33 rabbits was carried out using EBD m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…These findings align with previous clinical studies, in which gentamicin delivered via collagen ECM or directly to the surgical site reached concentrations in local tissues that exceeded 300 mg/L, whereas systemic exposure was limited to approximately 1‐2 mg/L 36,49 . It is worth noting that the blood volume of a rabbit is approximately 3% of the blood volume of a human (∼0.15 L in rabbits and 5 L in humans) 50,51 . Therefore, the concentration of gentamicin expected in the systemic circulation of a patient implanted with one gentamicin containing ECM envelope would be much lower than the levels observed in this rabbit study, and probably undetectable.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings align with previous clinical studies, in which gentamicin delivered via collagen ECM or directly to the surgical site reached concentrations in local tissues that exceeded 300 mg/L, whereas systemic exposure was limited to approximately 1‐2 mg/L 36,49 . It is worth noting that the blood volume of a rabbit is approximately 3% of the blood volume of a human (∼0.15 L in rabbits and 5 L in humans) 50,51 . Therefore, the concentration of gentamicin expected in the systemic circulation of a patient implanted with one gentamicin containing ECM envelope would be much lower than the levels observed in this rabbit study, and probably undetectable.…”
Section: Discussionsupporting
confidence: 89%
“…36,49 It is worth noting that the blood volume of a rabbit is approximately 3% of the blood volume of a human (∼0.15 L in rabbits and 5 L in humans). 50,51 Therefore, the concentration of gentamicin expected in the systemic circulation of a patient implanted with one gentamicin containing ECM envelope would be much lower than the levels observed in this rabbit study, and probably undetectable. However, low systemic exposure to gentamicin may be more relevant in older patients and those with pre-existing renal failure.…”
Section: Low Risk Of Systemic Exposure To Gentamicinmentioning
confidence: 59%
“…The EBD dilution test was used to estimate blood volume [ 12 , 13 ]. It was conducted on the same day of the CO breath test after breath sampling.…”
Section: Methodsmentioning
confidence: 99%
“…Blood volume is a parameter in the equation used to calculate RBC lifespan based on CO breath test results. The EBD dilution test was performed as described elsewhere with slight modifications [ 12 , 13 ]. Briefly, for each animal, an initial (blank) 1 mL blood sample was withdrawn from the auricular artery and 1 mL of 0.2% EBD solution in normal saline was injected into the marginal vein.…”
Section: Methodsmentioning
confidence: 99%
“…The blood volume of New Zealand white rabbits was estimated using this procedure, by injection of Evan’s blue dye into the marginal vein and serial blood samples were obtained from the auricular artery to estimate the concentration of the dye [8] . It has been observed that the mean blood volume values using this procedure (65.76 ml/kg) falls within the normal physiological range (45–70 ml/kg) in New Zealand white rabbits [5] .…”
Section: Methods Detailsmentioning
confidence: 99%